Blood flow after contraction and cuff occlusion is reduced in subjects with muscle soreness after eccentric exercise. (29th May 2017) - Souza‐Silva, E.; Christensen, S. W.; Hirata, R. P.; Larsen, R. G.; Graven‐Nielsen, T.
Abstract : Delayed onset muscle soreness (DOMS) occurs within 1‐2 days after eccentric exercise, but the mechanism mediating hypersensitivity is unclear. This study hypothesized that eccentric exercise reduces the blood flow response following muscle contractions and cuff occlusion, which may result in accumulated algesic substances being a part of the sensitization in DOMS. Twelve healthy subjects (five women) performed dorsiflexion exercise (five sets of 10 repeated eccentric contractions) in one leg, while the contralateral leg was the control. The maximal voluntary contraction (MVC) of the tibialis anterior muscle was recorded. Blood flow was assessed by ultrasound Doppler on the anterior tibialis artery (ATA) and within the anterior tibialis muscle tissue before and immediately after 1‐second MVC, 5‐seconds MVC, and 5‐minutes thigh cuff occlusion. Pressure pain thresholds (PPTs) were recorded on the tibialis anterior muscle. All measures were done bilaterally at day 0 (pre‐exercise), day 2, and day 6 (post‐exercise). Subjects scored the muscle soreness on a Likert scale for 6 days. Eccentric exercise increased Likert scores at day 1 and day 2 compared with day 0 ( P <.001). Compared with pre‐exercise (day 0), reduced PPT ( 25%, P <.002), MVC ( 22%, P <.002), ATA diameter ( 8%, P <.002), ATA post‐contraction/occlusion blood flow ( 16%, P <.04), and intramuscular peak blood flow ( 23%, P <.03) were found in the DOMS leg on day 2 but not in the control leg. These results showed that eccentric contractions decreased vessel diameter, impaired the blood flow response, and promoted hyperalgesia. Thus, the results suggest that the blood flow reduction may be involved in the increased pain response after eccentric exercise.